Synecology of rotifers in a tropical flood plain lake of upper Assam - SHARMA, B K (The Indian Journal of Animal Sciences, 2014)
Rotifera (37 species) comprised dominant qualitative component of zooplankton of Samuajan beel. Littoral and limlnetic communities included 35 and 33 species, indicated monthly richness of 4-1 G and 9-1 G spccies and rcglstel’ed 17.4 -71. 4 % and zero - 84.2 % community similarities. The former reflected abundance ranging between 17 and 138 ind’!l (57 Â± 34 ind/litre), depicted bimodal pattern and comprised between 17.1-71.4 % or total zooplankton. Limnetic rotifers (16-167 ind’/litre 54 Â± 42 ind’/htre) comprised between 14.3 and 69.6 % of zooplankton and indicated trimodal pattern. Comments are made on tempOIal variations in the rotifer abundance and on the factors influencing their production.